Proposed computer forensic approach for cloud computing environment - Ahmed, M. (American Scientific Publishers, 2016)
The security perimeter in computing has changed from a fixed boundary to an elastic boundary that is constantly changing and also the threats are evolving, making the Incident handler more difficult to analyze the information system based attacks. Therefore, the purposes of this study are introducing a new approach in identifying computer forensic attacks using Infrastructure as a Service (IaaS) in a cloud computing environment. First will identify and classify the different types of attacks on cloud infrastructure. Next, based on the attacks we are going to suggest an appropriate approach that can be utilized to collect as much data possible to perform a detailed investing of the incidents or attacks. Furthermore, the proposed approach will be tested in a virtual environment in order to check its effectiveness. Finally, refinement will be performed based on the results obtained and will be bench marked against the existing computer forensic approaches. Thus, this study contributes to better provide many data sources that can be used by the investigators to conduct forensics investigation in the infrastructure layer of the cloud computing. The findings will benefit the organizations which deploy private cloud services and infrastructure services which include virtual machines. Therefore, this paper discusses in detail the proposed computer forensic approach.